Chemical constituents from branches of Maytenus gonoclada (Celastraceae) and evaluation of antimicrobial activity - Silva,Fernando C (2011)
Six pentacyclic triterpenes were isolated from branches of Maytenus gonoclada (Celastraceae) and all NMR data of a new compound 3-oxo-12α,29-dihydroxyfriedelane are herein reported. The stereochemistry of the new friedelane was established by bidimensional NMR (HSQC, HMBC and NOESY) data, and its molecular weight confirmed by ESI mass spectrometry. Antimicrobial activity assays using the method of disk diffusion and macrodilution were carried out against the bacteria Escherichia coli, Citrobacter freundii, and Bacillus cereus, and against the fungi Candida albicans. The triterpene 3-oxo-12α-hydroxyfriedelane showed positive result against C. albicans.